Independent risk factors for a complicated hospital course in intensive care unit overdose patients. Issue 2 (17th September 2014) - Tarui, Takehiko; Yoshikawa, Kei; Miyakuni, Yasuhiko; Kaita, Yasuhiko; Tamada, Nao; Matsuda, Taketo; Miyauchi, Hiroshi; Yamada, Kenji; Matsuda, Takeaki; Yamaguchi, Yoshihiro
<x xml:space="preserve">Abstract</x> Aim The purpose of the present study was to identify risk factors associated with a complicated hospital course in overdose patients admitted to the intensive care unit. Methods A total of 335 overdose patients were retrospectively studied in the surgical and medical intensive care unit of an academic tertiary hospital. Factors possibly associated with a complicated hospital course were evaluated. Complicated hospital course was defined as the occurrence of pneumonia, rhabdomyolysis, decubitus ulcer, nerve palsy, prolonged intubation, prolonged hospitalization, or death. Results Of the 335 overdose patients, 93 (27.8%) had a complicated hospital course. Complicated hospital course was found to be associated with a high number of ingested pills (median, 135 [interquartile range, 78–240] versus 84 [53–134] tablets, P < 0.0001), low Glasgow Coma Scale score on admission (7 [3–11] versus 13 [8–15], P < 0.0001), and a high serum lactate level on admission (1.8 [1.0–3.0] versus 1.4 [0.9–2.0] mg/dL, P < 0.01) on univariate analysis of these factors in patients with and without a complicated hospital course. The independent risk factors for a complicated hospital course identified on multivariate analysis were a high number of ingested pills (≥100 tablets), low admission Glasgow Coma Scale score (<9), and high serum lactate on admission (≥2.0 mg/dL). The probability of a complicated hospital course for patients with 0, 1, 2, or all 3 independent risk factors were 7%, 22%, 40%, and 81%, respectively. Conclusion The total number of ingested pills, admission Glasgow Coma Scale score, and serum lactate level on admission are predictive of a complicated hospital course in overdose patients admitted to the intensive care unit.